3D kinematical analysis of the hammer throw in competitions - Mercadante, L. A.; Menezes, R. P.; Martini, T. P.; Trabanco, J. L. A.; Leite de Barros, R. M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
This study analyzes 14 throws accomplished in Brazilian competitions and it compares with available international results in the literature. It calculates the angle, the velocity and the height of release of the hammer and the velocity curves in function of the time, starting from the 3D trajectory of the head of the hammer. The analyses relate the difference between Brazilian (averages of 55.38m male and 52.05m female) and international results (averages of 79.44m male and 70.60m female) and the release velocity (Brazilian averages of 24.59m/s male and 23.59m/s female, and international of 29.60m/s male and 28.89m/s female). The velocity curves in function of the time of the international releases show that the accelerations are higher and the deceleration lower during the turns, when compared with a Brazilian throw.